CODE-SWITCHING AS A TEACHING AND LEARNING STRATEGY IN ESL CLASSROOMS - Lachmy Narayana A/L Jogulu, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
This research paper examines the phenomenon of code-switching in ESL classrooms in Malaysia, where English teachers often employ the Malay language as a support tool for teaching and learning. The study aims to investigate the reasons behind code-switching among students and lecturers in the English language classroom at Malaysian Polytechnics and explore how it contributes to their language acquisition goals. A descriptive qualitative research design was employed, and data were collected through self-administered questionnaires from English language lecturers and semester four students. The results reveal that both lecturers and students hold positive attitudes towards code-switching, recognizing its potential benefits in terms of language learning, teaching strategies, student comfort, and lesson comprehension. Lecturers employ code-switching for various purposes such as clarification, tension easing, explaining language differences, socializing, and rephrasing utterances. Students frequently code-switch to aid language learning, foster a comfortable learning environment, and improve comprehension. While lecturers exhibit more neutral perspectives, students express stronger agreement towards code-switching. The findings highlight the pedagogical implications of code-switching, emphasizing its value as a tool for language acquisition and the need for strategic use and gradual reduction as learners’ progress. Creating a supportive learning environment that balances code-switching with target language engagement is essential. By leveraging the benefits of code-switching and promoting active engagement with the target language, educators can create inclusive language learning environments that facilitate learners' overall language proficiency development.